2021
DOI: 10.3390/jcm10051007
|View full text |Cite
|
Sign up to set email alerts
|

Generalized Joint Hypermobility and Injuries: A Prospective Cohort Study of 185 Pre-Professional Contemporary Dancers

Abstract: Generalized joint hypermobility (GJH) has been mentioned as one of the factors associated with dance injuries, but the findings are inconclusive. This study aims to investigate whether GJH, based on different Beighton score cut-off points, is a potential risk factor for injuries in pre-professional dancers. Four cohorts of first-year pre-professional dancers (N = 185), mean age 19.1 ± 1.3 years, were screened on musculoskeletal functioning at the start of their academic year. The Beighton score was used to mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Existing studies have shown that the injury of modern and contemporary dancers has a high prevalence and many potential risk factors, but current research cannot determine the mechanism of injury caused by each factor. The differences in choreography techniques or training modes will also lead to different injury conditions for dancers ( 9 ). Some risk factors have not been confirmed in other studies, and some studies have found the opposite for some factors, such as BMI and gender ( 2 , 8 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Existing studies have shown that the injury of modern and contemporary dancers has a high prevalence and many potential risk factors, but current research cannot determine the mechanism of injury caused by each factor. The differences in choreography techniques or training modes will also lead to different injury conditions for dancers ( 9 ). Some risk factors have not been confirmed in other studies, and some studies have found the opposite for some factors, such as BMI and gender ( 2 , 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…The results show that the risk factors of injury are related to stress (a visual analog scale is used to measure stress scores), sex, BMI, injury history, and other factors. Meanwhile, the injury sites are mostly concentrated in the ankle joint and foot (6)(7)(8)(9). There are also many research studies (10)(11)(12)(13) on professional dancers in modern and contemporary dance companies.…”
Section: Introductionmentioning
confidence: 99%